Neurological manifestations and clinical outcomes in hospitalized patients with COVID-19: Retrospective cohort in a Peruvian hospital - Quispe-Moore, Luis (2024)
Background: Most of hospitalized patients with COVID-19 have had neurological manifestations. However, biomarkers for specific neurological manifestations and how these affect clinical outcomes are still unclear. Objective: To describe the frequency of neurological manifestations in patients hospitalized with COVID-19 and analyze their relationship with biomarkers and relevant clinical outcomes. Methods: This retrospective cohort study included adult patients hospitalized due to COVID-19 with at least one neurological manifestation. Headache, anosmia, ageusia, and polyneuromyopathy were classified as nonspecific neurological manifestations, whereas epileptic seizures, decreased level of consciousness, delirium, encephalitis, abnormal movements, ataxia, and cerebrovascular events as specific. Assessed associations: a) clinical and laboratory covariates with the presentation of a specific neurological manifestation; b) the relationship between specific neurological manifestation and COVID-19 severity, mechanical ventilation, and mortality; and c) duration of mechanical ventilation and polyneuromyopathy. Results: Of the 338 patients included in the study, 61,2% had severe COVID-19, 25,2% required mechanical ventilation, and 23,7% died. The most frequent neurological manifestations were headache (68,3%), delirium (41,9%), decreased level of consciousness (40,8%), and polyneuromyopathy (21,8%). High serum D-dimer levels and lymphopenia were associated with a specific neurological manifestation. At least one specific neurological manifestation was found in 39,9% of patients, and these group was associated with mechanical ventilation and mortality. Finally, a longer duration on mechanical ventilation was associated with a higher frequency of polyneuromyopathy. Conclusion: Specific neurological manifestations were frequent in hospitalized patients with COVID-19 and are associated with greater clinical and laboratory severity.